2021
DOI: 10.1155/2021/5523787
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Attitude towards Electronic Medical Record Systems: An Input for Future Implementers

Abstract: Background. Electronic medical record (EMR) systems offer the potential to improve health care quality by allowing physicians real-time access to patient healthcare information. The endorsement and usage of EMRs by physicians have a significant influence on other user groups in the healthcare system. As a result, the purpose of this study was to examine physicians’ attitudes regarding EMRs and identify the elements that may influence their attitudes. Method. An institutional-based cross-sectional study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 39 publications
0
31
1
Order By: Relevance
“…More than half (10/17,59%) of the studies reported on CDS tools, with 29% (5/17) of the studies investigating conventional CDS [ 62 , 63 , 66 , 67 , 71 ] and 29% (5/17) of the studies focusing on AI-based CDS [ 59 , 61 , 65 , 69 , 70 ]. Of the 17 studies, 6 (35%) focused on EHRs [ 58 , 60 , 64 , 68 , 73 , 74 ], whereas the remaining 1 (6%) study examined a remote patient-monitoring tool [ 72 ]. Of the 17 studies, 13 (76%) were solely based on qualitative individual semistructured interviews.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…More than half (10/17,59%) of the studies reported on CDS tools, with 29% (5/17) of the studies investigating conventional CDS [ 62 , 63 , 66 , 67 , 71 ] and 29% (5/17) of the studies focusing on AI-based CDS [ 59 , 61 , 65 , 69 , 70 ]. Of the 17 studies, 6 (35%) focused on EHRs [ 58 , 60 , 64 , 68 , 73 , 74 ], whereas the remaining 1 (6%) study examined a remote patient-monitoring tool [ 72 ]. Of the 17 studies, 13 (76%) were solely based on qualitative individual semistructured interviews.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 studies, the other 2 (12%) followed a mixed methods approach [ 61 , 64 ]. They conducted qualitative individual semistructured interviews and enriched their data with quantitative surveys using the 5-point Likert scale [ 66 , 74 ]. The studies were conducted in 26 different locations, with 6 (23%) studies conducted in the United States [ 58 , 59 , 62 , 65 , 68 , 70 ], 3 (12%) in the United Kingdom [ 67 , 68 , 71 ], 2 (8%) in Ireland [ 68 , 71 ], 2 (8%) in the Netherlands [ 69 , 72 ], and 2 (8%) in Australia [ 64 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Health professionals who had computer literacy, had 2.7 times more favorable attitude to EMR implementation as compared to those who had no computer literacy (AOR: 2.66; 95% CI: 1.16-6.09) and having good knowledge for EMR had 1.8 times more likelihood to have favorable attitude to EMR as compared to having poor knowledge (AOR: 1.8; 95% CI: 1.10-2.96) (Table 5). 20); computer access (10); hospital lack of management commitment and poor network had signi cant association with attitude status of health professionals towards EMR implementation. The difference might be due to management concern and commitment difference, budget difference among health institutions.…”
Section: Socio-demographic Characteristics Of Study Participantsmentioning
confidence: 99%